Preferences of pregnant women toward a future maternal Group B Streptococcus vaccine in China: A cross-sectional survey with a discrete choice experiment - Jiaxi Du; Wenjing Ji; Hang Zhao; David J. McIver; Yifei Zhao; Jie Chang; Yu Fang (Taylor & Francis Group, 2023)
ABSTRACTGroup B streptococcus (GBS) is a major cause of neonatal death worldwide. A GBS vaccine for pregnant women is under development and is expected to be available in the near future. The perceptions and preferences of pregnant women in China of GBS vaccines has not been investigated, and this study aimed to investigate pregnant women's awareness of GBS and their potential preferences for the GBS vaccine. A discrete choice experiment was conducted among pregnant women in hospitals from Shaanxi, Hunan, and Zhejiang provinces located in Western, Central, and Eastern China, respectively. A conditional logit model was used to analyze the data and calculate willingness to pay values and choice probabilities of different GBS vaccine programs. A total of 354 pregnant women were included in the final analysis, 45.8% of whom were willing to receive a GBS vaccine if it were licensed. Vaccine safety was the most important attribute of a future vaccine, while cost was the least important attribute. Compared with no vaccination, pregnant women had a strong preference for future GBS vaccination (ASC = 1.267, p < .001). Pregnant women's decisions were highly influenced by those of other pregnant women. Improving the safety, efficacy, and vaccination rate of the GBS vaccine in China is of great significance for future GBS vaccine development and vaccination. Compared to other variable options, the cost of a GBS vaccine was of the least importance among pregnant women in mainland China. These findings can inform public health policy decisions related to GBS vaccination in China.